Prioritizing Pathways Linking Educational Stress to Mental Health Outcomes: A Mixed-Methods Analysis Among Moroccan Students - Rodrigues da Silva, Diana; Benali, Youssef (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to identify and prioritize the key pathways through which educational stress influences mental health outcomes among students in Morocco using an integrated qualitative–quantitative framework.Methods and Materials: A sequential exploratory mixed-method design was employed. In the first phase, a qualitative thematic analysis was conducted through a systematic review of global and regional studies on educational stress and psychological well-being until theoretical saturation was achieved. The data were analyzed using NVivo 14, generating seven major themes: academic pressure, parental expectations, cognitive coping, peer climate, institutional factors, emotional outcomes, and resilience. In the second phase, a quantitative survey was administered to 160 Moroccan participants, including students and educators, who ranked the relative importance of the identified pathways using a five-point Likert scale. Data analysis was performed in SPSS 26, employing descriptive statistics, mean ranking, and Kendall’s coefficient of concordance (W = 0.81, p < 0.001) to assess inter-rater agreement.Findings: Results indicated strong consensus among participants regarding the hierarchical influence of stress pathways on mental health. Academic pressure and performance anxiety emerged as the most influential pathway (M = 4.62, SD = 0.48), followed by parental and societal expectations (M = 4.40, SD = 0.55) and cognitive appraisal and coping styles (M = 4.25, SD = 0.59). Peer relations, institutional environment, and emotional outcomes ranked moderately, while resilience and protective mechanisms (M = 3.54, SD = 0.72) were perceived as reactive but essential buffers against stress-induced distress.Conclusion: Educational stress is a multidimensional construct shaped by academic, familial, cognitive, and institutional dynamics. Addressing these interconnected pathways through targeted interventions—such as resilience training, institutional reform, and family-based awareness—can significantly enhance students’ mental health outcomes and academic sustainability in the Moroccan context.